PANDANGAN ISLAM TENTANG HAKASASI MANUSIA - Sumirat, Iin Ratna (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2013)
This. article discusses the Islamic veiw on human rights. The idea of human rights is generally viewed as a secular idea of West. This opinion seems incorrect. Doctrines of human rights, as a matter of fact, has existed in the tradition of world religions since more than a thousand years ago and has left moral foot-steps that could not be eliminated from the recent thoughts. The idea of human rights is also noted in the holy texts of Islam. In Islam, the idea of human rights is an important part of Islamic doctrines in which Islam guarantees and provides legitimation not only on political rights, but also on socio-economic rights of individuals. A lot of verses of Qur'an show how Islam appreciate and respect human rights and raise the position of humans among other creations. Key Words: Islam, West, Human Rights, Islamic Doctrines